2017
DOI: 10.1021/acs.cgd.7b00173
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Single Crystalline Titanium Oxide Nanoparticle Formation from a Two-Dimensional Nanowelded Network

Abstract: Nanostructured materials are gaining increasing importance due to their unique properties resulting from the high surface to volume ratio and the altered characteristics of the nanoscaled building blocks. The properties of these materials depend strongly on their microstructure and thus can be controlled by inducing transformation on the nanoscale. In this work, a simple low energy ion beam irradiation technique is presented that can be used to effectively weld the hydrogen titanate nanotubes into a large-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Subthreshold ionization also leads to a stacking fault . In previous ion irradiation studies on hydrogen titanate, the hydroxyl groups were partly removed due to collisional effects. Similar defects and stacking faults are known to form upon electron irradiation for various systems. Thus, the electron beam may lead to partial removal of the hydroxyl group from TiO 6 layered HTNW.…”
Section: Resultsmentioning
confidence: 99%
“…Subthreshold ionization also leads to a stacking fault . In previous ion irradiation studies on hydrogen titanate, the hydroxyl groups were partly removed due to collisional effects. Similar defects and stacking faults are known to form upon electron irradiation for various systems. Thus, the electron beam may lead to partial removal of the hydroxyl group from TiO 6 layered HTNW.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, our group reported large-scale joining of hydrogen titanate-based nanostructures for the formation of a 3D nano-network by ion irradiation [16]. Ion energy as low as 5 keV and ion fluence as low as 8×10 15 ions cm −2 showed welding between two titanate nanotubes [10]. The pristine cuprous oxide nanowires do not show any joining (figure 5 Apart from the surface morphology, significant changes in the crystal structure are observed in the XRD study after ion irradiation (figure 6).…”
Section: Morphological and Structural Property Analysismentioning
confidence: 99%
“…On the other hand, due to the curved surface and reduced dimensionality, the projectiles and recoils escape the nanowire easily compared to the thin-film or bulk structure, and hence the ion beam effects are different for nanowire and bulk. A handful of studies performed on oxide materials demonstrated surface modifications experimentally at nanoscale [9,10]. However, the formation mechanism and effect of such surface modifications are not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…Figure c shows the coexistence of two different types of nanostructures with thicker nanorods of an average diameter of about 120 ± 20 nm which are WO 3 with lengths in the range of 1–5 μm . The thinner nanotube is H 2 Ti 3 O 7 with an average diameter of 15 ± 5 nm and length in the range of 1–5 μm. , A high-magnification FESEM image shows that the HTNTs are uniformly distributed on the surface of WO 3 NRs and wrapped around them (also shown in supplementary Graph S3­(c)). Figure d shows the TEM image of a pristine core–shell of 1D H 2 Ti 3 O 7 @ WO 3 , where HTNTs cover the tungsten oxide nanorods.…”
Section: Resultsmentioning
confidence: 90%
“…44 The thinner nanotube is H 2 Ti 3 O 7 with an average diameter of 15 ± 5 nm and length in the range of 1−5 μm. 38,45 A highmagnification FESEM image shows that the HTNTs are uniformly distributed on the surface of WO 3 NRs and wrapped around them (also shown in supplementary Graph S3(c)). Figure 1d shows the TEM image of a pristine core−shell of 1D H 2 Ti 3 O 7 @ WO 3 , where HTNTs cover the tungsten oxide nanorods.…”
Section: ■ Results and Discussionmentioning
confidence: 97%